The interaction of acousnic and electromagnetic fields in a mixture of electrolytes - L. M. Kuzmina; V. M. Rylyuk; M. I. Skipa (Геофизический журнал, 2016)
Nonlinear mechanism of interaction of acoustic and electromagnetic fields is considered. It is shown that the sound wave propagating in a mixture solution of electrolytes is able to induce an alternating electromagnetic fields of the acoustic range and presence of an external source of electromagnetic radiation in the region of the sound wave propagation leads to the appearance an additional acoustic harmonics. The strength of the induced magnetic field and the magnitude of sound pressure of harmonics are calculated. The conditions of the magnetic acoustic resonance, which leads to the appearance of the constant magnetic field and the sound pressure of additional acoustic harmonics, are considered.